A systematic review and meta-analysis of physical exercise prehabilitation in major abdominal surgery: (PROSPERO 2017 CRD42017080366) - Heger, Patrick; Probst, Pascal; Wiskemann, Joachim; Steindorf, Karen; Diener, Markus K.; Mihaljevic, André Leopold (Journal of gastrointestinal surgery, 2020)
Physical exercise prehabilitation has been proposed to improve postoperative outcomes in patients undergoing major abdominal surgery. The aim of this systematic review was to investigate the effect of preoperative exercise training compared with standard care on postoperative outcomes in major abdominal surgery.
Published online: 21 June 2019
Gesehen am 13.08.2020